The Effect Of Fluctuations Of Variables (oil Price, Degree Of Economic Openness, Terms Of Trade) On The Real Exchange Rate In Algeria For The Period (1980-2018) - Moussaoui, Soumaia; Benzaoui, Abdrazak (Université de M'sila, 2020)
Abstract: The objective of this study is to show the relationship between the effects of the variables, namely, oil prices, degree of economic openness, conditions of economic exchange on the real exchange rate in Algeria, Focusing on the crisis of the two oil crises of 1986, 2014 and the most important effects of the monetary variables of the Algerian economy, which depends on its exports to oil, The study concluded that there is a long relationship between the real exchange rate variable and the oil price, the degree of economic openness and terms of trade exchange, as explained by the error correction model. Keywords: Oil prices, terms of trade, degree of economic openness, real exchange rate. JelClassificationCodes: : G34 Résumé: L'objectif de cette étude est de montrer la relation entre les effets des variables que sont les prix du pétrole, le degré d'ouverture économique, les conditions d'échange économique sur le taux de change réel en Algérie, en se concentrant sur la crise des deux crises pétrolières de 1986 , 2014 et les effets les plus importants des variables monétaires de l'économie algérienne, qui dépend de ses exportations vers le pétrole, L'étude a conclu qu'il existe une longue relation entre la variable du taux de change réel et le prix du pétrole, le degré d'ouverture économique et les termes de l'échange, comme l'explique le modèle de correction d'erreur. Mots clés : Prix du pétrole, termes de l'échange, degré d'ouverture économique, taux de change réel. JelClassificationCodes :G34 ملخص: تهدف هذه الدراسة إلى إظهار العلاقة بين آثار المتغيرات والتي تتمثل في أسعار النفط، درجة الانفتاح الاقتصادي، شروط التبادل الاقتصادي على سعر الصرف الحقيقي في الجزائر، مركزين على الأزمة الأزمتين النفطيتين لسنتي 1986،2014 وأهم الآثار التي مست المتغيرات النقدية للاقتصاد الجزائري الذي يعتمد في صادراته على النفط، وتوصلت هذه الدراسة من خلال الجانب التطبيقي بأن هناك علاقة طويلة بين متغير سعر الصرف الحقيقي وأسعار النفط، درجة الانفتاح الاقتصادي وشروط التبادل التجاري وهذا ما أوضحه نموذج تصحيح الخطأ. الكلمات المفتاحية: أسعار النفط، شروط التبادل التجاري، درجة الانفتاح الاقتصادي، سعر الصرف الحقيقي.
Keywords: الكلمات المفتاحية: أسعار النفط، شروط التبادل التجاري، درجة الانفتاح الاقتصادي، سعر الصرف الحقيقي.